Determinants of consumer attitude toward corporate sponsors: A comparison between a profit and nonprofit sport event sponsorship. Issue 2 (9th October 2016) - Ko, Yong Jae; Chang, Yonghwan; Park, Chanmin; Herbst, Frikkie
Abstract: The purposes of the present study were to identify key attributes of sponsors that positively influence consumers' attitude formation and to examine the moderator role of sport event types (nonprofit vs. profit). Based on the theories of range and selective attention, we hypothesized that consumers weigh differently on particular sponsorship attributes depending on event type (i.e., profit vs. nonprofit) in constructing their attitude. The study utilized multi‐group structural equation modeling on data collected by questionnaire survey from a total of 505 spectators of college sport event ( n  = 303) and FIFA World Cup ( n  = 202). Results of structural equation modeling test indicate that prominence of sponsors is an important predictor of consumer attitude in both events, while sincerity of sponsors was found to be important in local and amateur college sport event sponsorship. From a theoretical perspective, the current study sheds light on sponsorship study, particularly the importance of examining sponsor characteristics in predicting consumer attitude and the event type as a moderating variable. A key practical implication is that sport managers should carefully examine consumers' perceptions toward sponsor characteristics in making their event sponsorship decisions. Copyright © 2016 John Wiley & Sons, Ltd.